Impact of Transarterial Chemoembolization on 1 year survival rate of Patients suffering from Non-resectable Hepatocellular Carcinoma (Medical Forum Monthly, 2024)
Objective: Treatment of nonresectable HCC remains unsatisfactory and different therapeutic regimes have been tested. Transarterial chemoembolization (TACE) is the most promising palliative modality for unresectable HCC and determination of the survival rates of patients after TACE is important to guide clinicians for proper management of advanced HCC. So objective of our study was to determine 1 year survival rate in patients with unresectable HCC treated by TACE.Study Design: Retrospective Study.Place and Duration of Study: This study was conducted at Shaukat Khanum Cancer Hospital & Research Centre, Lahore from July 2009 to June 2010.Materials and Methods: 90 patients with unresectable HCC who underwent TACE treatment were identified from a prospectively collected database. Patient survival from the first TACE session was calculated at 6 and 12 months duration after TACE, with Kaplan-Meier analysis.Results: A total of 90 patients were studied. All patients underwent TACE with appropriate technical measures. The age range of patients was 34 years to 84 years. Mean age of patients was calculated to be 59.67 years and median to be 58yrs. 59 were males and 31 were females. In all 90 patients, none died because of the complications of TACE. 3 out of these 90 patients died within 6 months of procedure, while 11 died within 1 year. So this resulted in 14 patients out of 90 (15%), who could not survive after 1 year of TACE. 76 patients remained alive with survival rate of 84.4%.Conclusion: TACE is an effective treatment option for advanced unresectable HCC. Our study showed that, the overall survival benefit for such patients is tremendously improved if they are managed with TACE.